Ocena kosztów trudności finansowych polskich spółek giełdowych sektora informatyki - Manikowski, Arkadiusz (Calculating of Leverage Cost for Polish Public Companies from Informatics Sector, 2005)
Effect of financing companies activity by debt is cost of leverage. This cost, which is not considered in classical capital structures models of Modigliani and Miller, influence on market value of firms. Up to present many another models of capital structure with leverage cost are elaborated. Well-known are Damodaran and Fernandez ones. This article deal with calculating of leverage cost in Polish circumstance by using Damodaran model. Mentioned analysis was realized on public firms from informatics sector. Obtained results allow to make correctly valuation of companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 231-244